Analysis of the Organizational Culture Influence on Online Services at UPI Libraries During the Covid-19 Pandemic - Maharani, Anindya Putri (Edulib, 2021)
The COVID-19 pandemic that has occurred for almost 3 years has become a new challenge, especially libraries in reorganizing the services they provide to visitors. Meanwhile, the library as an institution / organization requires stable management through its organizational culture. The urgency of this research is to analyze whether the characteristics of organizational culture, especially in the scope of innovation and risk taking, care and responsiveness, have an effect on the services provided and become a consideration. This research method uses a qualitative approach with analytical descriptive methods. The main instruments used were interview guidelines and questionnaires. The data were obtained from a population of FIP students, with a sample of representatives of departments in FIP (a total of 9 majors). It was concluded that the characteristics of the organizational culture will affect the online services provided by the UPI library. Through the characteristics of organizational culture, libraries are able to identify the needs of librarians and of course provide the best service. There are also several online services that users find helpful during this pandemic. In future studies, it is hoped that quantitative research methods can be used so that the data obtained will be processed with certainty and concrete values.